Pharmaco-behavioral profiling identifies suppressors of autism gene–associated phenotypes in zebrafish - Priyanka Jamadagni; Yi Dai; Yunqing Liu; Hellen Weinschutz Mendes; April Pruitt; Suha Khan; Liang Yang; Tzu-Chieh Huang; Xiayuan Huang; P. J. Michael Deans; Novin Balafkan; Dejian Zhao; et al. (Proceedings of the National Academy of Sciences, 2026)
Pharmaco-behavioral screens in scalable in vivo systems have critical advantages for drug discovery relevant to large-effect autism spectrum disorder (ASD) genes. Here, we establish a database and open-source website of the behavioral signatures of 520 US Food and Drug Administration (FDA)-approved drugs using high-throughput assays of basic sensory processing and arousal behaviors in larval zebrafish. By leveraging the behavioral profiles of 9 large-effect ASD gene mutants, we identify enrichment of pharmacological mechanisms that anticorrelate with subgroups of ASD genes with shared behavioral phenotypes. Screening of anticorrelating drugs in mutants of two ASD genes, SCN2A and DYRK1A , uncovers compounds that suppress mutant behavioral phenotypes. We identify estropipate, an estrogen receptor agonist, and paclitaxel, a microtubule inhibitor, as the top suppressors in scn1lab and dyrk1a mutants, respectively, and levocarnitine (LEVO), a mitochondrial modulator and carnitine supplement, as a top suppressor of both mutant behavioral phenotypes. Finally, we find that LEVO rescues regional brain activity deficits and dysregulated lipid metabolic pathways in mutants, as well as signaling deficits in human pluripotent stem cell–derived glutamatergic neurons carrying mutations in SCN2A and DYRK1A , demonstrating conservation of drug rescue across systems. Therefore, our study establishes a pharmaco-behavioral resource for precision medicine-based drug discovery, illuminating targets relevant to large-effect ASD genes.